JENIS-JENIS KAPANG YANG DITEMUKAN PADA LEMANG BERAS HITAM (Oryza sativa Siarang) - Osnita, Syovia; Periadnadi, Periadnadi; Fifendy, Mades (Pendidikan Biologi, 2013)
ABSTRACT Lemang is a traditional food from West Sumatera. Generally, lemang is made of black sticky rice or white sticky rice. In Talang Babungo, is made of black rice (not sticky rice) and still can be consumed eventhough it has been kept for days and has be taken by mould. The purpose of this research is to discover the varieties of mould which exists in black rice lemang.  This  research  uses descriptive survey method  by isolating mould,  making pure seedling, and then identifying. The result of isolating and identifying are found five varieties of mould in that lemang, those are Aspergillus niger, Aspergillus ustus, Aspergillus sp, Mucor racemosus, and Penicillium expansum.